Deconstruction and Reconstruction of Femininity in Macbeth from the Perspective of Androgyny - Yang, Xinli (Randwick International of Social Science Journal, 2025)
Woolf’s theory of the "androgynous mind," Freud’s concept of "repetition compulsion," and Foucault’s theory of disciplinary power together illuminate the deeper causes of Lady Macbeth’s tragic fate in Macbeth. In her attempt to transcend traditional gender roles, Lady Macbeth represses her feminine ethical traits and excessively amplifies masculine qualities such as cruelty and decisiveness. This imbalance in gender characteristics leads to intense inner conflict. At the same time, the internalization of social disciplinary power infiltrates her thoughts and behaviors, distorting her understanding of power and identity. As a result, she becomes both a replication of patriarchal logic and a victim of psychological collapse due to her inability to escape gender constraints. The interplay between psychological structure and social discipline reveals the multilayered roots of her tragedy, offering a new theoretical perspective for gender criticism of Shakespeare’s female characters.